2020
DOI: 10.1038/s41390-020-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid exome sequencing in PICU patients with new-onset metabolic or neurological disorders

Abstract: Background: Genomic assessment previously took months to result and was unable to impact clinical care in the pediatric intensive care unit (PICU). The advent of rapid exome sequencing potentially changes this. We investigated the impact of rapid exome sequencing in a pilot study on pediatric patients admitted to a single PICU with new onset metabolic/neurologic disease. Methods: Rapid exome sequencing (7 days to verbal result) was performed on (n=10) PICU patients age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…With the exception of one non-randomized retrospective study looking at a longer turnaround time exome test, 27 studies performed in the carefully controlled environment of clinical research have reproducibly found genome-wide sequencing to be effective for diagnosis and management of undiagnosed infants in ICUs and to result in reductions in health care costs. 6,8,11,[14][15][16][20][21][22][28][29][30][31][32][33][34] PBB demonstrates the feasibility of deploying rWGS-informed RPM into routine care across multiple sites to help vulnerable patients in a cost-effective manner while achieving diagnosis and change-in-medical-care rates comparable to previously published studies. Test results influenced the decisions physicians and families made about the care of babies with rare genetic diseases.…”
Section: Discussionmentioning
confidence: 75%
“…With the exception of one non-randomized retrospective study looking at a longer turnaround time exome test, 27 studies performed in the carefully controlled environment of clinical research have reproducibly found genome-wide sequencing to be effective for diagnosis and management of undiagnosed infants in ICUs and to result in reductions in health care costs. 6,8,11,[14][15][16][20][21][22][28][29][30][31][32][33][34] PBB demonstrates the feasibility of deploying rWGS-informed RPM into routine care across multiple sites to help vulnerable patients in a cost-effective manner while achieving diagnosis and change-in-medical-care rates comparable to previously published studies. Test results influenced the decisions physicians and families made about the care of babies with rare genetic diseases.…”
Section: Discussionmentioning
confidence: 75%
“…Cost-effectiveness should be reassessed as well using systematic review as the literature increases but interim findings are encouraging. 91 Workforce considerations will change including ordering providers, need of clinical geneticists/ genetic counselors, and lab availability.…”
Section: Monitoring and Evaluationmentioning
confidence: 99%
“…[8][9][10] Previous work has demonstrated that rapid genome-wide sequencing (ultra-rapid whole-genome sequencing [urWGS], rapid whole-genome sequencing [rWGS], or rapid whole-exome sequencing [rWES]) is associated with both a shorter time to diagnosis and an increased diagnostic yield when compared with standard-of-care testing, including gene panels and chromosome microarrays. 6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, earlier diagnosis of genetic disorders is a process measure and not a definitive mark of clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…26 Although 15 studies to date have shown, by varying definitions, the clinical utility of rapid genome-wide sequencing in the NICU, PICU, and CVICU, it is not yet clear what the specific indications for such testing should be, nor, beyond case series, in what situations urWGS, rWGS, or rWES are associated with improved outcomes. 6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]33 Moreover, modeling of previously published data suggests that both the cost and clinical utility of urWGS, rWGS, and rWES vary inversely with time to result. 14,16 However, the optimal match of presentations, timeliness, and cost effectiveness is not yet known.…”
Section: Introductionmentioning
confidence: 99%